KOMUNIKASI INTERPERSONAL ANTARA PENDAMPING DAN ORANG TUA DALAM PENDAMPINGAN ANAK TERINFEKSI HIV/AIDS DI KOTA PEKANBARU - Johan Situmorang; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Having HIV / AIDS is often regarded as a disgrace, because the stigma directed at HIV / AIDS sufferers is often associated with deviant people and has an environment of promiscuity and unhealthy sexual intercourse. HIV cases in children are caused by transmission from their mother. This is a double burden for parents of children with HIV / AIDS (ADHA). With the peer companion (PS) in helping to strengthen and motivate parents, interpersonal communication is very important for ADHA's companion and parents. The purpose of this study was to determine interpersonal communication between companions and parents in assisting children infected with HIV / AIDS in Pekanbaru City as seen from the attitude of openness, empathy, positive behavior, supportive attitudes and equality between the companion and ADHA parents. This study used a qualitative method, the subject of the informant was selected using a purposive technique. The informants in this study were 4 people, namely 2 peer assistants and 2 parents of children with HIV / AIDS. The data collection techniques used in this study were interviews, observation and documentation. The technique of data analysis is by collecting data, reducing data, presenting data, drawing conclusions and evaluating by using the data validity checking technique, namely triangulation. The results showed that interpersonal communication between companions and parents in assisting children infected with HIV / AIDS in Pekanbaru was quite good. ADHA's companion and parents both showed mutual openness The openness of the companion with ADHA's parents happened slowly and started with creating a sense of comfort. The empathetic attitude of the companion is shown in the attention they give to the child's condition. Mentors often ask parents about their child's condition, then remind them to routinely carry out drug therapy, and motivate them to have a normal life expectancy like the others. While positive behavior is expressed by the companion by being an example for ADHA parents that routine treatment of antiretroviral drugs (ARV) can help children to continue to live like normal people, as experienced by their own companions. Accompanying support to ADHA parents is to provide understanding and information about HIV that will help them feel calm and motivated. the chaperone shows equality to ADHA's parents by considering their relationship as friends and relatives. Keyword: Interpersonal Communication, Companion, HIV / AIDS